Halomonas gemina sp. nov. and Halomonas llamarensis sp. nov., two siderophore-producing organisms isolated from high-altitude salars of the Atacama Desert - Hintersatz, Christian; Singh, Shalini; Rojas, Luis Antonio; Kretzschmar, Jerome; Wei, Sean Ting-Shyang; Khambhati, Khushal; Kutschke, Sabine; Lehmann, Falk; Singh, Vijai; Jain, Rohan; Pollmann, Katrin (Frontiers in Microbiology, 2023)
Introduction This study aimed to identify and characterize novel siderophore-producing organisms capable of secreting high quantities of the iron-binding compounds. In the course of this, two not yet reported halophilic strains designated ATCHAT and ATCH28T were isolated from hypersaline, alkaline surface waters of Salar de Llamará and Laguna Lejía, respectively. The alkaline environment limits iron bioavailability, suggesting that native organisms produce abundant siderophores to sequester iron. Methods Both strains were characterized by polyphasic approach. Comparative analysis of the 16S rRNA gene sequences revealed their affiliation with the genus Halomonas. ATCHAT showed close similarity to Halomonas salicampi and Halomonas vilamensis, while ATCH28T was related closest to Halomonas ventosae and Halomonas salina. The ability of both strains to secrete siderophores was initially assessed using the chromeazurol S (CAS) liquid assay and subsequently further investigated through genomic analysis and NMR. Furthermore, the effect of various media components on the siderophore secretion by strain ATCH28T was explored. Results The CAS assay confirmed the ability of both strains to produce iron-binding compounds. Genomic analysis of strain ATCHAT revealed the presence of a not yet reported NRPS-dependant gene cluster responsible for the secretion of siderophore. However, as only small amounts of siderophore were secreted, further investigations did not lie within the scope of this study. Via NMR and genomic analysis, strain ATCH28T has been determined to produce desferrioxamine E (DFOE). Although this siderophore is common in various terrestrial microorganisms, it has not yet been reported to occur within Halomonas, making strain ATCH28T the first member of the genus to produce a non-amphiphilic siderophore. By means of media optimization, the produced quantity of DFOE could be increased to more than 1000 µM. Discussion Phenotypic and genotypic characteristics clearly differentiated both strains from other members of the genus Halomonas. Average nucleotide identity (ANI) values and DNA–DNA relatedness indicated that the strains represented two novel species. Therefore, both species should be added as new representatives of the genus Halomonas, for which the designations Halomonas llamarensis sp. nov. (type strain ATCHAT = DSM 114476 = LMG 32709) and Halomonas gemina sp. nov. (type strain ATCH28T = DSM 114418 = LMG 32708) are proposed.